5. KEBIJAKAN PEMERINTAH AMERIKA SERIKAT TERHADAP KEJAHATAN LINGKUNGAN AKIBAT PENCEMARAN LINGKUNGAN OLEH PERUSAHAAN MULTINASIONAL BRITISH PETROLEUM DI TELUK MEKSIKO TAHUN 2010 - Widiastari, Stefani Gestananda; Utomo, Tri Cahyo; Paramasatya, Satwika (Journal of International Relations, 2016)
Environmental pollution in Gulf of Mexico became the most acute environmental pollutionin United States (US). Pollution caused by negligence committed intentionally by officerBritish Petroleum (BP) oil pipeline resulted in the explosion happened. Omissionscommitted intentionally and caused certain damage to the environment can be categorizedas an environmental crime.Environmental contamination by BP became a threat for thenational security of the United States, as evidenced by the US government attention givento contamination occurs. One concern that was given is when President Barrack Obamacanceled a visit abroad to observe firsthand the pollution incident. This study aims todetermine the policy set by the US government in dealing with pollution case made by BPin 2010. The framework that used in this research are transnational environmental crime,public policy and precautionary principle. The type of this research is descriptiveexplanativewith qualitative data analysis techniques through data collection technique.The result of this research is an explanation about determination of the US government’spolicy in dealing with cases of environmental pollution the Gulf of Mexico, there are theestablishment of national commission, the determination of the provision of fines from theUS government to BP, agreement between BP and Environmental Protection Agency(EPA) and recovery program Gulf of Mexico.